Approximate controllability of semilinear impulsive functional differential systems with non-local conditions. (4th February 2020) - Arora, Sumit; Singh, Soniya; Dabas, Jaydev; Mohan, Manil T
Abstract: This paper is concerned with the approximate controllability of semilinear impulsive functional differential systems in Hilbert spaces with non-local conditions. We establish sufficient conditions for approximate controllability of such systems via resolvent operator and Schauder's fixed point theorem. An application involving the impulse effect associated with delay and non-local conditions is presented to verify our claimed results.